2012
DOI: 10.1097/scs.0b013e31824cd81a
|View full text |Cite
|
Sign up to set email alerts
|

Signs and Symptoms of Temporomandibular Dysfunction in Fibromyalgic Patients

Abstract: Thus, there is a high prevalence of signs and symptoms of TMD in FM patients, indicating the need for an integrated diagnosis and treatment of these patients, which suggest that the FM could be a medium- or long-term risk factor for the development of TMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 18 publications
0
33
0
12
Order By: Relevance
“…A study on patients with fibromyalgia [19] showed that the most common signs are pain in masticatory muscles, in the TMJ, articular click in jaw opening; the aforementioned study defined cephalea and facial pain as symptoms; moreover, the prevalence of; myofascial pain was found.…”
Section: Discussionmentioning
confidence: 99%
“…A study on patients with fibromyalgia [19] showed that the most common signs are pain in masticatory muscles, in the TMJ, articular click in jaw opening; the aforementioned study defined cephalea and facial pain as symptoms; moreover, the prevalence of; myofascial pain was found.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion was that the comorbidity between TMD and fibromyalgia is due to central sensitization, with high levels of substance P and growth factor causing a compromise in thalamic function (21). That same year, Fraga et al concluded that MTMD should be included as diagnostic criteria in fibromyalgia (22). 29% of MTMD patients refer the presence of Dizziness/Vertigo vs 19.4% in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Using this classification, almost all patients with FM are women because they have more tender points than do men [4]. Overall, FM symptoms lead to significant reduction in functional capacity and quality of life [2, 5, 6]. Developing treatment teams is useful, including clinicians with expertise in patient education, exercise training interventions, and cognitive behavioral therapy [79].…”
Section: Introductionmentioning
confidence: 99%
“…A key issue is the association of FM with other musculoskeletal comorbidities, such as temporomandibular dysfunction (TMD) [5]. It has been shown that TMD can develop as a result of mandibular compression during daily living activities and sleep in the patients with FM [57], in which the coexistence of these pathologies generates a clinical outcome of high complexity [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation